An Indirect Comparison of Efficacy and Safety of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Disoproxil Fumarate and Abacavir/Lamivudine + Dolutegravir in Initial Therapy. - Josep M Llibre; François Raffi; Graeme Moyle; Georg Behrens; Stephane Bouee; Geraldine Reilly; Peter Borg; David Piontkowsky; Felipe Rogatto (PLoS ONE)
Objectives The objective of this analysis is to perform an indirect comparison of elvitegravir, cobicistat, emtricitabine and tenofovir DF (E/C/F/TDF) to abacavir/lamivudine and dolutegravir (ABC/3TC + DTG) by using 2 trials evaluating each of these regimens in comparison to efavirenz, emtricitabine and tenofovir DF (EFV/FTC/TDF). Methods An indirect comparison was performed by using a generalization of Bucher's methodology to calculate risk differences. Two phase III clinical trials (GS-US-236-0102 and SINGLE-described above) were used. Results Results of the indirect comparison showed no statistically significant risk difference of the efficacy endpoint of achieving HIV RNA < 50 copies/mL between E/C/F/TDF and ABC/3TC + DTG for the ITT population at weeks 48, 96 and 144: respectively -3.7% (CI95% = [-10.8%; 3.4%]), -5.2% (CI95% = [-13.2%; 2.8%]) and -3.1% (CI95% = [-12.0%; 5.7%]). There was no statistically significant differences in the risk difference for serious adverse events (5.7% (CI95% = [-2.2%; 12.3%])), drug related adverse event (2.7% (CI95% = [-7.0%;12.4%])), drug related serious adverse event (0.8% (CI95% = [-1.6%;3.2%])) and death (0.5% (CI95% = [-0.8%;1.8%])), respectively, between E/C/F/TDF and ABC/3TC + DTG. A significant difference was found for discontinuation due to adverse events with a higher rate for E/C/F/TDF (difference = 8.6% (CI95% = [3.3%; 13.9%])). There was also no statistically significant risk difference of the viral resistance of 1.2% (CI95% = [-1.2; 3.7]) between E/C/F/TDF and ABC/3TC + DTG at week 48, 1.7% at week 96 (CI95% = [-1.1; 4.5]) and 2.2% (CI95% = [-1.0; 5.4]) at week 144.